(untitled) (Revista Argentina de Cirugía, 2021)
Appendiceal mucinous neoplasms are rare and represent 0.2-0.7% of all appendectomies. They usual present as an incidental finding. The diagnosis can be made during the evaluation of chronic abdominal pain in the right lower quadrant or may emerge in the pathology report in the setting of an acute appendicitis. Appendectomy is the treatment of choice and care must be taken to avoid perforation of the appendix with dissemination of neoplastic cells or mucus into the peritoneum and thus prevent the development of pseudomyxoma peritonei.